МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ РОЗПОДІЛУ НАПРУГИ ВЗДОВЖ ОБВИТОК ТРАНСФОРМАТОРА ЗА ДІЇ НА НИХ ІМПУЛЬСНИХ ПЕРЕНАПРУГ - Сегеда, М.С.; Черемних, Є.В.; Химюк, І.В.; Мазур, Т.А.; Курулишин, О.М. (Інститут електродинаміки НАН України, Київ, 2015)
A mathematic model for the investigation of the wave processes in the windings of the transformer was suggested. The method of separation of variables was used for solving the integral-differential equations. Stress distribution along the windings under the impulse surges was studied. References 5, figure 1.